Important nonsense: Yeats and symbolism - Dwan, D (Johns Hopkins University Press, 2019)
This essay shows how the practice of symbolism needs to be interpreted within a broader intellectual history. The metaphysical content of this history might encourage us to abandon it, but it provides the conditions of intelligibility, nonetheless, for key literary concepts–at least if one assumes that the historical operation of these concepts have some bearing on their current use. I make the case with Yeats. His symbolic practice, I argue, is unintelligible without reference to two metaphysical traditions in which he was deeply invested 1) an idealism that is pledged to a super-reality that exceeds time and space 2) a radical subjectivism in which the private ego is the source and ground of meaning in the world. The friction between these two outlooks partly explains why the symbol becomes such a "troubled mirror" in Yeats's writing.